The Development and Initial Validation of a Self-Report Job Precariousness Scale Suitable for Use With Young Adults Who Study and Work. (November 2020) - Creed, Peter A.; Hood, Michelle; Selenko, Eva; Bagley, Louella
Precarious employment has been increasing worldwide. Yet there are few scales suitable to assess it, and no scales to measure perceived job precariousness in working students who are particularly vulnerable. Using classic test theory, we generated 21 job precariousness items and had them reviewed by experts. In Study 1 ( N = 282, 63% female, mean age 22 years), exploratory factor analysis yielded four factors of job conditions, security, remuneration, and flexibility, each with 3 items. In Study 2 ( N = 211, 75% female, mean age 22 years), confirmatory factor analysis confirmed that this four-factor model was the best fit compared to unidimensional, second-order, and bifactor models. Cronbach's α coefficients for all factors and the full-scale score were sound (all >.78). Validity was supported by showing that precariousness was related negatively to life satisfaction and employer support and positively to job insecurity, financial strain, and subjective social status. Precariousness was unrelated to age, sex, and hours worked. The Job Precariousness Scale has the potential to promote research into the effects of precarious employment on working students' current and future functioning and achievement and how experiences of precariousness influence the development of a precarity identity.